DEVELOPMENT OF BIOMAGAZINE-BASED LKPD IN ECOSYSTEM MATERIAL IN CLASS X OF STATE HIGH SCHOOL 10 PALANGKA RAYA - Fahrina, Ririn; _, Erni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2024)
LKPD is a learning facility and guideline to support learning activities to be active and interactive so that it makes it easier for students to achieve learning goals. Based on the observation results, it shows that there are limitations in teaching materials in the form of LKPD which still do not support the learning needs of students. Teachers use package books in which there are brief assignments and practicum activities as learning guidelines without directly facing students on problems related to the material, and the LKPD used is not interesting and complete. The purpose of the study is to determine the feasibility of the product and the response of students to the biomagazine-based LKPD development product on ecosystem material in class X of SMA Negeri 10 Palangka Raya. The development method with the Hannafin and Peck model consists of three phases, namely Analysis, Design, and Development and Implementation where all stages involve the evaluation and revision process. The data collection instrument is a validation questionnaire of material experts, media, language, and student responses. LKPD is tested in small-scale stages. The results of the development research resulted in a biomagazine-based LKPD product with the results of development suitable for use in learning in schools. This is based on data obtained from the assessment of the feasibility of LKPD by material experts of 77.65%, media experts 80%, linguists 98.57%, and student responses of 97.65%.